A lesser evil: why democracies fail to push back against cyber election interference - Laudrain, A (2024)
Recent episodes of foreign meddling into elections in the past decade have led observers asking whether democracies could uphold their electoral sovereignty in the 21st Century. Free and fair elections are the cornerstone of democratic regimes, and such encroachment on a Nation’ sovereignty and self-determination would be expected to trigger a strong response from the affected states. Yet, what we have witnessed in terms of foreign policy response ranges from unspecified threats and diplomatic sanctions to total inaction. How can we explain this variation?